Energy and quality of service management in wireless multimedia sensor networks - Pereira, Paulo (2013)
Sensor networks are composed of resource constrained nodes that capture data from the environment, preprocess it and then transmit it to a sink node. This paper presents a scenario for monitoring an electricity distribution network, an energy analysis of the used sensor nodes and an intelligent energy and quality of service (QoS) manager. This manager continuously adapts the provided QoS according to the energy level of the nodes.